Aplikasi Hugelkultur dengan Raised Bed Pada Pertumbuhan dan Produktivitas Tanaman Pakcoy (Brassica rapa L.) - Ria Dwi Jayati; Fitria Lestari (Jurnal Biosilampari : Jurnal Biologi, 2023)
This research aims to determine the effect of hugelkultur application with raised beds on the growth and productivity of Brassica rapa L. The type of research used was experimental research with a completely randomized design (CRD) using 3 treatments and 9 replications. The treatment details are P1 (hugelkultur planting media with raised bed), P2 (conventional planting media with raised bed), P3 (conventional planting media with polybags). This research was carried out in Karang Jaya, Selupu Rejang District, Rejang Lebong Regency, Bengkulu Province in September-November 2023. The research data were analyzed using one-factor ANOVA using SPSS 16, if there were variations between treatments then continued with LSD. The conclusion of the research was that the application of hugelkultur planting media with a raised bed showed that there were differences in the growth and productivity of Brassica rapa L., plants in each treatment with the parameters of plant height, number of leaves, leaf width and wet weight. The results of the ANOVA statistical test showed that there was an influence of the application of hugelkultur planting media with raised beds on the productivity growth of Brassica rapa L.